1978
DOI: 10.1104/pp.62.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of Nitrogen Nutrition and Photosynthesis in Pisum sativum L

Abstract: Physiological responses to infection by strains of Rhizobium leguminosarum which differed in their capacity to reduce N2 were determined in 26-day-old pea plants (Pisum sadvum L. cv. Alaska) grown under uniform environmental conditions in the absence of combined N. The highest N2 reduction rates, calculated from H2 evolution and C2H2-dependent C2H4 production measurements, were approximately 6-fold greater than the lowest. Higher N2 fixation rates were associated with greater CO2 exchange rates (R2 = 0.92) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 5 publications
1
19
1
1
Order By: Relevance
“…Thus, within the concept of the two opposing processes (21) stimulation due to enhanced P uptake no longer occurred, whereas competition for carbohydrates determined host growth response. Although compensatory CO2 fixation by the host plant in response to increased carbohydrate requirements by microsymbionts have been noted in the past (4,23), the conclusion that the host will meet higher demand by increased production (25) has not been verified by the results of this experiment, perhaps due to limitations on photosynthesis caused by suboptimal light conditions. Low levels of light intensity have been shown to depress nodulation (10) and VAM fungal development (17).…”
Section: Discussioncontrasting
confidence: 46%
“…Thus, within the concept of the two opposing processes (21) stimulation due to enhanced P uptake no longer occurred, whereas competition for carbohydrates determined host growth response. Although compensatory CO2 fixation by the host plant in response to increased carbohydrate requirements by microsymbionts have been noted in the past (4,23), the conclusion that the host will meet higher demand by increased production (25) has not been verified by the results of this experiment, perhaps due to limitations on photosynthesis caused by suboptimal light conditions. Low levels of light intensity have been shown to depress nodulation (10) and VAM fungal development (17).…”
Section: Discussioncontrasting
confidence: 46%
“…Energy lost to H2 production probably was minimized in strains 128C53 and 92F 1 by hydrogenase activity. These strains also had relatively low rates of total H2 production and high rates of C2H2 reduction (Table I) (3). Dixon (9) demonstrated that different species of host plants induced various levels of uptake hydrogenase activity in Rhizobium bacteroids.…”
Section: N2 Fixation Parametersmentioning
confidence: 99%
“…The present experiments were performed to separate the effects of ontogeny and growth irradiance on nitrogenase and hydrogenase activity in Rhizobium leguminosarum 128C53. In addition, other strains of this bacterial species were examined for hydrogenase and nitrogenase activity in vivo to determine the mechanisms underlying different N2 reduction rates which alter photosynthetic efficiency (3). MATERIALS to control diffusion of gas through the needle.…”
mentioning
confidence: 99%
“…Indeed, even with the cost to the plant of reduced photosynthate by as much as 14% [87], rhizobia have been demonstrated to increase the rate of photosynthesis and other associated measures in common bean (intercellular CO 2 concentration and the transpiration rate) [70], peas [88] and soybean [87]. Rhizobial colonization of the non-legume crop rice increased photosynthetic rate, stomatal conductance, transpiration velocity, water utilization efficiency and flag leaf area.…”
Section: Agricultural Value Of G Diazotrophicusmentioning
confidence: 99%